Islamic financial system in the national legislation framework: courts cases analysis - Syed Yusuf, Sharifah Norzehan; Mohamed Adil, Mohamed Azam; Lateh, Najahudin; Md Rejab, Siti Noorbiah (2012)
The legal framework of the Islamic financial system in Malaysia is still under the purview of the Civil law. This is because the Federal Constitution which divides the jurisdiction of the Civil and Shari'ah matters is silent on whether the Shari'ah Court has the power to hear cases or disputes relating to Islamic finance. As a result, this leads to many interpretations of the civil courts in contractual and financial applications which are contrary to the principles of Shari'ah Law. This raise questions about the extent to which Islamic financial framework can be operational in the existing legal situation? Henceforth, this study will be focusing on the results and interpretations of the Civil Court in cases of Islamic finance and banking. The study employs qualitative method in viewing the Islamic financial system under the country's legal framework through analysis of court cases in an attempt to produce a new proposal to strengthen the Islamic financial practices. For data collection, the researchers used different types of textual study through library and field research. In addition, interviews were conducted to gather the data. This study suggests several amendments in the Federal Constitution and relevant Acts in enhancing the existing laws and role of Shari'ah courts.